2019
DOI: 10.1088/1748-9326/ab4240
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater temperature anomalies in central Europe

Abstract: As groundwater is competitively used for drinking, irrigation, industrial and geothermal applications, the focus on elevated groundwater temperature (GWT) affecting the sustainable use of this resource increases. Hence, in this study GWT anomalies and their heat sources are identified. The anthropogenic heat intensity (AHI), defined as the difference between GWT at the well location and the median of surrounding rural background GWTs, is evaluated in over 10 000 wells in ten European countries. Wells within th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
33
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 69 publications
0
33
0
1
Order By: Relevance
“…Especially when the shallow subsurface is dominated by horizontal flow, changes in atmospheric temperatures and land use represent thermal signals that are conduced to the aquifer and become visible in well-logs. These changes are pronounced in cities, where accelerated heat flux from urban warming, sealed ground, and buried infrastructures yields large scale subsurface urban heat islands (Ferguson and Woodbury, 2004;Menberg et al, 2013;Zhu et al, 2015;Benz et al, 2016;Epting et al, 2017;Bayer et al, 2019;Hemmerle et al, 2019), and urban, industrial and waste sites are revealed to cause the most prominent local heat anomalies in Central European aquifers (Tissen et al, 2019). In less-disturbed rural areas, groundwater temperatures are reported to slowly increase as well, which is obviously the response of the shallow ground to recent climate change (Maxwell and Kollet, 2008;Bloomfield et al, 2013;Kurylyk et al, 2014;Menberg et al, 2014;Colombani et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Especially when the shallow subsurface is dominated by horizontal flow, changes in atmospheric temperatures and land use represent thermal signals that are conduced to the aquifer and become visible in well-logs. These changes are pronounced in cities, where accelerated heat flux from urban warming, sealed ground, and buried infrastructures yields large scale subsurface urban heat islands (Ferguson and Woodbury, 2004;Menberg et al, 2013;Zhu et al, 2015;Benz et al, 2016;Epting et al, 2017;Bayer et al, 2019;Hemmerle et al, 2019), and urban, industrial and waste sites are revealed to cause the most prominent local heat anomalies in Central European aquifers (Tissen et al, 2019). In less-disturbed rural areas, groundwater temperatures are reported to slowly increase as well, which is obviously the response of the shallow ground to recent climate change (Maxwell and Kollet, 2008;Bloomfield et al, 2013;Kurylyk et al, 2014;Menberg et al, 2014;Colombani et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In urban areas anthropogenic impacts, such as a dense building development, underground car parks, open geothermal systems and injections of thermal wastewater from industry result in local thermal alteration of groundwater up to several degrees (e.g. Taylor and Stefan, 2009;Zhu et al, 2011;Menberg et al, 2013b;Tissen et al, 2019). According to Brielmann et al (2011) annual temperature fluctuations in aquifers, caused by shallow geothermal energy systems, range between 4 °C in winter and 20 °C in summer.…”
mentioning
confidence: 99%
“…Due to the hydrophobic nature of hydrocarbons, the dissolution in water is low (Mackay et al 2006 ) and microorganisms will face them as drops in the water and / or adsorbed to soil and sediments. Groundwater temperatures in central Europe [10–12 °C (Tissen et al 2019 )] will also result in hydrocarbons larger than C 15 being present in the solid stage, which will further reduce bioavailability. To overcome the bioavailability issues, some degrading microorganisms are known to produce biosurfactants.…”
Section: Introductionmentioning
confidence: 99%